Consensus on the diagnosis, prognosis, and treatment of canine and feline mammary tumors: solid arrangement – 2023 - Cassali, Geovanni Dantas; Nakagaki, Karen Yumi Ribeiro; Jark, Paulo César; Horta, Rodrigo dos Santos; Arias, Alejandro Cervantes; Tellado, Matías Nicolás; Estrela-Lima, Alessandra; Sueiro, Felipe Augusto Ruiz; Reys, Marina Possa dos; Wronski, Júlia Gabriela; Sierra, Oscar Rodrigo; Kristancic, Edie Avila; et al. (Brazilian Journal of Veterinary Pathology, 2024)
The purpose of this paper is to discuss and update the criteria that guide the diagnosis, prognosis, and treatment of canine and feline neoplasms. This work was developed during the 5th Meeting of Mammary Pathology and the 1st Latin American Congress of Mammary Pathology, held on October 5th and 6th, 2023, in Belo Horizonte, MG, Brazil. The event was organized by the Laboratory of Comparative Pathology, Department of General Pathology, ICB/UFMG, with the support of the Brazilian Association of Veterinary Pathology (ABPV), Brazilian Veterinary Oncology Association (ABROVET) and the Latin American Society of Veterinary Oncology (SLOVET). The primary goal of the meeting was to unite academics and professionals in veterinary mammary oncology to discuss the morphology, diagnostics criteria, and prognosis of solid mammary tumors in dogs and cats, and to provide updates on treatment guidelines for mammary tumors.